An assessment of bioactive compounds and antioxidants in some tropical legumes, seeds, fruits and spices - LL, Dilworth; KJ, Brown; RJ, Wright; MS, Oliver; HN, Asemota (Journal of Research in Biology, 2014)
Objective: The main objective of this research was to assess bioactive compounds, antioxidant potential and mineral concentration of commonly consumed foods as well as underutilized ones for improved health and food security. Methods: Twelve food samples were assessed for minerals, flavonoids, IP6, total polyphenols and antioxidant activity. IP6 was determined by anion exchange chromatography while flavonoids, polyophenols, minerals and antioxidant activity were determined by standard methods. Results: The highest concentrations of IP6 were recorded in legumes and corn while appreciable levels were also found in golden apple and sorrel samples. The highest concentrations of flavonoids and total polyphenols were found in non-leguminaceaous samples. Pimento and ginger samples recorded highest antioxidant activity (p<0.05) with values comparable to the standard ascorbic acid while pumpkin seeds and onion samples recorded lowest antioxidant activities. Mineral concentrations varied with the samples of pimento, golden apple and sorrel having highest calcium concentrations. Sorrel, ginger and pimento recorded highest iron concentrations, while zinc levels were as highest in both hulled and unhulled pumpkin seed samples. Okra samples recorded the highest copper concentrations. Conclusion: Food samples analysed are rich in minerals, bioactive compounds and antioxidants hence their increased exploitation for nutraceutical and nutritional benefits are advocated. Data from this study argues well for increased production and consumption of rarely consumed pumpkin and jackfruit seeds in light of their nutritional profile and antioxidant activity. Most samples assessed are valuable in supplementing nutrient-poor diets.